Arsenic removal from soil with high iron content using a natural surfactant and phosphate - Mukhopadhyay, S.; Hashim, M.A.; Allen, M.; Sen Gupta, B. (2014)
An environment friendly arsenic removal technique from contaminated soil with high iron content has been studied. A natural surfactant extracted from soapnut fruit, phosphate solution and their mixture was used separately as extractants. The mixture was most effective in desorbing arsenic, attaining above 70 % efficiency in the pH range of 4–5. Desorption kinetics followed Elovich model. Micellar solubilization by soapnut and arsenic exchange mechanism by phosphate are the probable mechanisms behind arsenic desorption. Sequential extraction reveals that the mixed soapnut–phosphate system is effective in desorbing arsenic associated with amphoteric–Fe-oxide forms. No chemical change to the wash solutions was observed by Fourier transform-infrared spectra. Soil:solution ratio, surfactant and phosphate concentrations were found to affect the arsenic desorption process. Addition of phosphate boosted the performance of soapnut solution considerably. Response surface methodology approach predicted up to 80 % desorption of arsenic from soil when treated with a mixture of ≈1.5 % soapnut, ≈100 mM phosphate at a soil:solution ratio of 1:30.